Multi-criteria optimization in terms of fuzzy criteria definitions - Raskin, Lev; Sira, Oksana; Sagaydachny, D. (Lviv Polytechnic National University, 2018)
The problems of multi-criteria optimization are considered. Known methods for solving these problems are generalized to the case when weights that take into account the relative importance of particular criteria are not clearly defined. The procedure for constructing membership functions of fuzzy numbers, given by sets of intervals of possible values, using a linearized computation of least squares methods is substantiated. In this case, for the description of fuzzy numbers, the membership functions of (L-R)-type were chosen. A method for solving a fuzzy multi-criteria optimization problem for a scalarized criterion is proposed. The technology of solving the problem reduces it to a linear fractional problem of mathematical programming. A converging iterative procedure for finding the optimal plan is described. An alternative method for solving the original fuzzy problem based on the formation of a Pareto-set of non-dominated options is considered. To solve this problem, a procedure has been proposed for comparing fuzzy numbers using a probability-theoretic approximation of their membership functions.

Розглянуто задачi багатокритерiальної оптимiзацiї. Вiдомi методи розв’язання цих задач узагальнено на випадок, коли ваговi коефiцiєнти, що враховують вiдносну важливiсть окремих критерiїв, визначенi нечiтко. Обґрунтовано процедуру побудови функцiй приналежностi нечiтких чисел, заданих наборами iнтервалiв можливих значень, що використовує лiнеаризовану обчислювальну схему методу найменших квадратiв. Для описiв нечiтких чисел вибрано функцiї приналежностi (L-R)-типу. Запропоновано метод розв’язування нечiткої задачi багатокритерiальної оптимiзацiї для скаляризованого критерiю. Технологiя розв’язування задачi зводить її до дробово-нелiнiйної задачi математичного програмування. Описано збiжну iтерацiйну процедуру знаходження оптимального плану. Розглянуто альтернативний метод розв’язування нечiткої задачi на основi формування Парето-множини недомiнуючих варiантiв. Для розв’язання цiєї задачi запропоновано процедуру порiвняння нечiтких чисел з використанням теоретико-ймовiрнiсної апроксимацiї їх функцiй приналежностi.
Багатокритерiальна оптимiзацiя в умовах нечiтко визначених важливостей критерiїв
Keywords: multi-criteria optimization; fuzzy source data; optimization of a fractional non-linear functional; Pareto-set; багатокритерiальна оптимiзацiя; нечiткi вихiднi данi; оптимiзацiя дробово-нелiнiйного функцiонала; Парето-множина